Exercise Decreases Lipogenic Gene Expression in Adipose Tissue and Alters Adipocyte Cellularity during Weight Regain After Weight Loss - Giles, Erin D.; Steig, Amy J.; Jackman, Matthew R.; Higgins, Janine A.; Johnson, Ginger C.; Lindstrom, Rachel C.; MacLean, Paul S. (Frontiers in Physiology, 2016)
Exercise is a potent strategy to facilitate long-term weight maintenance. In addition to increasing energy expenditure and reducing appetite, exercise also favors the oxidation of dietary fat, which likely helps prevent weight re-gain. It is unclear whether this exercise-induced metabolic shift is due to changes in energy balance, or whether exercise imparts additional adaptations in the periphery that limit the storage and favor the oxidation of dietary fat. To answer this question, adipose tissue lipid metabolism and related gene expression were studied in obese rats following weight loss and during the first day of relapse to obesity. Mature, obese rats were weight-reduced for 2 weeks with or without daily treadmill exercise (EX). Rats were weight maintained for 6 weeks, followed by relapse on: a) ad libitum low fat diet (LFD), b) ad libitum LFD plus EX, or c) a provision of LFD to match the positive energy imbalance of exercised, relapsing animals. 24h retention of dietary- and de novo-derived fat were assessed directly using 14C palmitate/oleate and 3H20, respectively. Exercise decreased the size, but increased the number of adipocytes in both retroperitoneal (RP) and subcutaneous (SC) adipose depots, and prevented the relapse-induced increase in adipocyte size. Further, exercise decreased the expression of genes involved in lipid uptake (CD36 & LPL), de novo lipogenesis (FAS, ACC1), and triacylglycerol synthesis (MGAT & DGAT) in RP adipose during relapse following weight loss. This was consistent with the metabolic data, whereby exercise reduced retention of de novo-derived fat even when controlling for the positive energy imbalance. The decreased trafficking of dietary fat to adipose tissue with exercise was explained by reduced energy intake which attenuated energy imbalance during refeeding. Despite having decreased expression of lipogenic genes, the net retention of de novo-derived lipid was higher in both the RP and SC adipose of exercising animals compared to their energy gap-matched controls. Our interpretation of this data is that much of this lipid is being made by the liver and subsequently trafficked to adipose tissue storage. Together, these concerted effects may explain the beneficial effects of exercise on preventing weight regain following weight loss.